Batman forever [videorecording (DVD)] - Schumacher, Joel, 1939-2020-; Kilmer, Val, 1959-; Jones, Tommy Lee, 1946-; Carrey, Jim, 1962-; Kidman, Nicole, 1967-; O'Donnell, Chris; Barrymore, Drew (2005)
Robin has teamed up with Batman, and this time evil is in the guise of The Riddler and Harvey 'Two Face' Dent. Batman has added tension as psychologist Chase Meridian is anxious to find out who Batman is.